In Vitro Synthesis of Adenovirus Core Proteins - Eron, Larry (1974)
mRNA extracted from polysomes of KB cells at late stages of productive infection with adenovirus type 2 was translated in a cell-free system derived from Krebs II ascites cells. Two of the polypeptides obtained in this reaction corresponded to the adenovirus core protein V and the precursor to core protein VII. The following criteria were used to establish identity between the in vitro products and the virion proteins: comigration during sodium dodecyl sulfatepolyacrylamide gel electrophoresis, cochromatography in sodium dodecyl sulfate-hydroxyapatite, specific immunoprecipitation of the precursor to core protein VII, and tryptic peptide analysis.